Description of a New Genus and New Species of Soft Scale Insect (Hemiptera: Coccomorpha: Coccidae) from Cuba. (6th July 2018) - Mestre-Novoa, Nereida; Kondo, Takumasa
A new neotropical genus and species of soft scale insect from Cuba, Hamonicoccus Mestre and Kondo gen. nov. is described and Hamonicoccus alayoi Mestre and Kondo sp. nov. (Hemiptera: Coccomorpha: Coccidae) is described and illustrated based on the adult female. The species was collected in Cayos de las Cinco Leguas, Matanzas Province, on Capparis cynophallophora (Capparaceae), and in Surgidero de Batabanó, Mayabeque Province, on Rhizophora mangle (Rhizophoraceae). The affinities of H alayoi sp. nov. with closely related species is discussed based on published literature. An updated list of soft scale insects (Hemiptera: Coccidae) known from Cuba is provided.